Psychosocial Burden of Itch among Renal Transplant Recipients - Piotr K. Krajewski; Kinga Tyczyńska; Klaudia Bardowska; Piotr Olczyk; Magdalena Krajewska; Jacek C. Szepietowski (Toxins, 2022)
Itch is the most common symptom of chronic dermatoses. Moreover, itch may be associated with systemic disorders. Chronic kidney disease—associated itch (CKD-aI) may affect up to 20% of renal transplant recipients (RTR). The aim of the study was to assess psychosocial burden of itch in RTR. The study was performed on a group of 129 RTR, out of which 54 (41.9%) experienced itch in the previous 3 days. A specially designed questionnaire assessing anxiety, depression, stigmatization, and quality of life was used. Results: Patients suffering from itch in the previous 3 days achieved significantly higher scores in GAD-7 (p < 0.001), BDI (p < 0.001), HADS total score (p < 0.001), HADS Depression (p = 0.004), and HADS Anxiety (p < 0.001). Severity of itch correlated positively with HADS, stigmatization scale, and GAD-7. Itch in RTR was associated with higher incidence of depression assessed with BDI (OR 3.7). Moreover, higher prevalence of anxiety was found among patients suffering from CKD-aI, assessed with HADS A and GAD-7 (OR 2.7 and OR 4.8, respectively) The results of our study clearly demonstrate that itch among RTR is a significant burden. Higher prevalence of depression and anxiety in this groups indicate the necessity of addressing itch relief as a part of holistic approach to patients after renal transplantation.